Life (online): an introduction to the #AoIR2020 special issue. Issue 6 (26th April 2021) - Hutchinson, Jonathon; Kerr, Aphra
ABSTRACT: Our contemporary life is an intertwined arrangement of 'Life' with digital technologies. Increasingly, we are seeing the prevalence of automation and machines, predominantly through artificial intelligence (AI), as a means to make sense of our worlds, engage with our employers, understand the political system and interact with our social lives as some of the key methods among a wide variety of other interpersonal communication processes. Not only are these often machine-based activities seen through digital communication itself, but also in the surrounding regulatory systems, the growing concerns of digital inequality, the act of datafication, and the infrastructures that enable and inhibit digital communication. These are some of the key themes that emerged from the selected papers in this special issue emerging from the 2020 Association of Internet Researchers (AoIR) conference, entirely held online and themed around 'Life'. In this special issue, we present seven papers from senior and emerging scholars within Asia, Europe, Africa, and North and South America that address and unpack the contemporary moment of communication in our Life. The papers in this special issue discuss chatbots, games, smart lighting, wearables, doorbells, sensors, biometrics, and facial recognition technology - – very much everyday technologies that shape many of our lives. They ground our expectations of AI and highlight the importance of context in internet research.